The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10531-005-5045-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of grazing practices on the plant and dipteran communities of a turlough in Co. Mayo, Ireland

Abstract: Turloughs, which are classified as priority habitats under the European Habitats Directive, are seasonally flooded depressions found almost exclusively in Ireland. In 2001, three adjacent fields with different stocking densities were selected and plant=dipteran communities within the same vegetation zone of each field (site) were investigated using quadrats and sweep netting, respectively. There was a significant positive relationship between Diptera morphospecies richness=Diptera abundance and mean vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…In fact, abundances of these groups did not differ between AES and control pastures. Reductions in species richness and/or abundance, and changes in species composition, have been observed in these groups in more intensively managed grassland (Siepel 1990;Gibson et al 1992;Kruess and Tscharntke 2002a;Ryder et al 2005;Zurbrügg and Frank 2006). However, such differences as there are between AES and control pasture management have not altered sward height between them, which is likely to be the strongest determinant of abundance of these groups.…”
Section: Foliar Invertebratesmentioning
confidence: 99%
“…In fact, abundances of these groups did not differ between AES and control pastures. Reductions in species richness and/or abundance, and changes in species composition, have been observed in these groups in more intensively managed grassland (Siepel 1990;Gibson et al 1992;Kruess and Tscharntke 2002a;Ryder et al 2005;Zurbrügg and Frank 2006). However, such differences as there are between AES and control pasture management have not altered sward height between them, which is likely to be the strongest determinant of abundance of these groups.…”
Section: Foliar Invertebratesmentioning
confidence: 99%
“…Previous studies show that grazing managements in grasslands can lead to either lower (Gonzalez-Megias et al, 2004;Joern, 2005;Littlewood, 2008), or higher insect abundance and richness (Cagnolo et al, 2002;Ryder et al, 2005;Debano, 2006;Rosa-García et al, 2009). Such conflicting results might partly derive from the difference in grazing intensity (Kruess and Tscharntke, 2002b;Cease et al, 2012), grazing season (Fonderflick et al, 2014), and grazer species (Dolek and Geyer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although much work has focused on the hydrology (Coxon 1987b), and the plant (MacGowran 1985), aquatic invertebrate (Bilton and Lott 1991;Tobin and McCarthy 2004;O'Connor et al 2004), and beetle (Good and Butler 2001;Ní Bhriain et al 2002) communities of turloughs, only one study to date by Ryder et al (2005), has considered Sciomyzidae on turloughs. Ryder et al showed that species richness and abundance patterns of Sciomyzidae followed those of dipteran morpho-species (in 33 other families) under three different management regimes, indicating that Sciomyzidae could be sensitive indicators of grazing.…”
mentioning
confidence: 99%